Analisis Fisikokimia dan Aktivitas Antibakteri Madu Hutan Timor terhadap Methicillin-Resistant Staphylococcus aureus - Undari, Fajar Okta; Latif, Hadri; Sudarwanto, Mirnawati Bachrum (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2025)
The emergence of antibiotic-resistant bacteria has become a global concern. One of the bacteria that is resistant to several types of antibiotics is Methicillin-Resistant Staphylococcus aureus (MRSA). Honey is known for its nutritional and antibacterial properties. The antibacterial activity of honey is due to several factors such as its physicochemical properties, H2O2, and phytochemicals compounds. Honey could be a promising alternative to overcome the problem of antibiotic resistance. The aim of this research was to determine the physicochemical, H2O2, Pinocembrin, Kaempferol and antimicrobial activity of Timor Forest honey. A total of 7 Timor Forest honey was analyzed to determine water content, water activity, pH, H2O2, Pinocembrin, Kaempferol and antibacterial activity. Moisture content, water activity, and pH were measured using a refractometer, aw-meter, and pH meter, respectively. Hydrogen peroxide content was measured using peroxide strip test. Pinocembrin and Kaempferol contents were measured using HPLC-DAD. The analysis showed that the water content, water activity and pH of Timor Forest honey were 17.52±3.31%, 0.6±0.01, 4.18±0.32, respectively. The content of H2O2, Pinocembrin, and Kaempferol were 109.1±47.1 µmol/L, 2.2±1.9 mg/100 g, 1.7±0.7 mg/100 g, respectively. The antibacterial activity of Timor Forest honey against MRSA was tested using Kirby-Bauer disc diffusion method. Vancomycin was used as positive control. The inhibition zone of Timor Forest honey and vancomycin was not significantly different with an average of 13.93±0.23 mm for Timor Forest honey and 14.33±0.05 mm for vancomycin. Timor forest honey has good physicochemical properties with a relatively high content of Pinocembrin and Kaempferol and has antibacterial activity against MRSA.